2019
DOI: 10.1002/tcr.201900068
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of Highly Efficient Light‐Emitting Layers in OLEDs with Dimesitylboranes: An Updated Review

Abstract: With excellent luminescent properties and transport properties, triarylborane compounds containing two mesitylenes (Mes) have gained much attention for their application in OLEDs as light‐emitting layers. This study serves as an updated review summarizing recent developments in the design of fluorescent chromophores and phosphorescent host materials for OLEDs comprising small molecular compounds of dimesitylborane (BMes2) as luminescent layers, with attention to the performance of different light‐emitting devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…The further increase of fw lead to the increase of emission intensity and blue shifts of PL spectra due to the increasing amount of aggregates. The similar regularities were observed for the compounds 2-4, 6 and were in good agreement with those reported for many other AIE/AIEE compounds [33][34][35]. However, slightly different behavior was observed for compound 5 (Figure 5b).…”
Section: Plqy % Nmsupporting
confidence: 91%
“…The further increase of fw lead to the increase of emission intensity and blue shifts of PL spectra due to the increasing amount of aggregates. The similar regularities were observed for the compounds 2-4, 6 and were in good agreement with those reported for many other AIE/AIEE compounds [33][34][35]. However, slightly different behavior was observed for compound 5 (Figure 5b).…”
Section: Plqy % Nmsupporting
confidence: 91%
“…This suggests potential utility also as materials for optoelectronic device or imaging applications. After the first demonstration by Shirota and co-workers that bithiophene or terthiophene with Mes 2 B substituents can be used as efficient electron-transporting materials in OLEDs, many different luminescent materials based on tricoordinate organoboranes have been designed. , More recently, researchers have discovered organoborane donor–acceptor systems that exhibit highly effective thermally activated delayed fluorescence (TADF) and even room temperature phosphorescence (RTP). Relevant to our studies is the work by Zhao and co-workers, who reported that triarylborane–triarylamine systems with [2.2]­paracyclophane, twisted biphenyl, or binaphthyl backbones display charge transfer emissions that, depending on the system, are temperature-dependent, are circularly polarized, or exhibit TADF characteristics. Of note is also work by Thilagar and co-worker, who designed simple structures exhibiting TADF, which encompass tridurylboranes with NR 2 (R = H, Me) donor moieties . In all these compounds, the spatial separation of the donor-centered HOMO and acceptor-centered LUMO plays an important role in enabling the TADF behavior .…”
Section: Resultsmentioning
confidence: 99%
“…Benefiting from a readily accessible low-lying vacant p z orbital on boron, triarylboranes serve important roles both as electron acceptors and as powerful Lewis acids . Their electron-deficient character and desirable photophysical properties are exploited in applications ranging from nonlinear optics to organic light-emitting diodes, organic field-effect transistors, and organic photovoltaics. , The tunable Lewis acidity of triarylboranes is advantageous in anion sensing, catalysis, and small molecule activation. Following the successful implementation of organoboranes in “frustrated Lewis pairs” (FLPs) chemistry by Stephan, , they have been applied in numerous catalytic processes including hydrogenation, hydroamination, and CO 2 reduction. The high Lewis acidity of organoboranes also facilitates catalytic hydrosilylation based on a weak Lewis acid (LA)–Lewis base (LB) interaction between boron and hydrosilanes. In all these processes the use of organoboranes as organocatalysts avoids the need for transition metal complexes that are oftentimes expensive and/or toxic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 35,36 These molecular probes, called AIEgens, can overcome ACQ through emission owing to the restriction of intermolecular bond rotations (RIR) and the proscription of energy dissipation upon aggregation. 37 They exhibit high quantum efficiency, good biocompatibility and photo-stability and therefore, find an assortment of applications in diverse fields such as chemo-/bio-sensors, 38,39 electroluminescent materials, 40 cell imaging, 41 optical devices 42 etc. 43 Among the reported AIE-gens, tetraphenylethylene (TPE) is one of the most studied luminophores due to its easy synthesis and simple functionalization strategies for the construction of novel sensing systems and various other applications.…”
Section: Introductionmentioning
confidence: 99%